Effect of interferon on concentrations of cyclic nucleotides in cultured cells. - Tovey, M G (1979)
Constant intracellular concentrations of both adenosine 3',5'-cyclic-monophosphate (cyclic AMP) and guanosine 3',5'-cyclic-monophosphate (cyclic GMP) were obtained when leukemia L1210 cells were cultivated under steady-state conditions in the chemostat. In this sensitive and controlled system addition of mouse interferon resulted in a rapid (5-10 min) increase in the intracellular concentration of cyclic GMP, which preceded by several hours an increase in the intracellular concentration of cyclic AMP. In contrast to the effect of interferon, addition of prostaglandin E1 induced a rapid increase in the intracellular concentration of cyclic AMP without markedly affecting the intracellular concentration of cyclic GMP. It is suggested that the rapid effect of interferon on cyclic GMP plays a role in mediating some of the effects of interferon on cells.